Clinical and prognostic role of sarcopenia in elderly patients with classical Hodgkin lymphoma: a multicentre experience. Issue 4 (11th June 2021) - Zilioli, Vittorio Ruggero; Albano, Domenico; Arcari, Annalisa; Merli, Francesco; Coppola, Alessandra; Besutti, Giulia; Marcheselli, Luigi; Gramegna, Doriana; Muzi, Cristina; Manicone, Moana; Camalori, Manuela; Ciammella, Patrizia; et al.
Abstract: Background: Elderly classical Hodgkin lymphoma (cHL) (ecHL) is a rare disease with dismal prognosis and no standard treatment. Fitness‐based approaches may help design appropriate treatments. Sarcopenia has been associated with an increased risk of treatment‐related toxicities and worse survival in various solid tumours, but its impact in ecHL is unknown. The aim of this retrospective multicentre study was to investigate the prognostic role of sarcopenia in ecHL. Methods: We included newly diagnosed >64 years old cHL patients who performed a baseline comprehensive geriatric assessment and high‐dose computed tomography (CT) or 18fluorine‐fluorodeoxyglucose positron emission tomography/CT before any treatment. Sarcopenia was measured as skeletal muscle index (SMI, cm 2 /m 2 ) by the analysis of high‐dose CT or low‐dose positron emission tomography/CT images at the L3 level. The specific cut‐offs for the SMI were determined by receiver operator curve analysis and compared with those proposed in literature and studied in diffuse large B‐cell lymphoma. Survival functions [progression‐free survival [PFS] and overall survival (OS)] were calculated for the whole population and for different subgroups defined as per different sarcopenia cut‐off levels. Results: We included 154 patients (median age 71 years old, 76 female). The median L3‐SMI was 42 cm 2 /m 2 . The specific cut‐off derived in our male population was 45 cm 2 /m 2 ; using this cut‐off, 27 male patients (35%) were defined as sarcopenic. After a median follow‐up of 5.9 years, the overall 5‐year PFS and OS rates were 53% and 65%, respectively, and were significantly shorter in sarcopenic male patients compared with non‐sarcopenic (PFS 31% vs. 61%, P = 0.008; OS 51% vs. 74%, P = 0.042). Applying diffuse large B‐cell lymphoma‐derived sarcopenic thresholds, there were no significant differences between sarcopenic and non‐sarcopenic patients for both PFS and OS, with a sole exception of a significant reduced PFS in sarcopenic male patients using Namakura cut‐off. The comprehensive geriatric assessment‐determined frail functional status was an independent adverse prognostic factor for both female and male patients. Conclusions: Baseline evaluation of sarcopenia through radiological examinations performed for ecHL staging may help define a proportion of male patients with unfavourable outcome with current treatment strategies. Also the functional status evaluation could allow to identify a frail subgroup of patients with worse outcome.